Pedagogical Innovations in Teacher Training and Qualification in Bulgaria - Galya Kozhuharova (ARPHA Proceedings, 2019)
The development of informational and communicational technologies and the changes in perception of today’s society requires a new look at the educational process of contemporary students which then leads to a newer vision of teachers’ qualification. Informational technologies are often seen as the only source of innovation. Innovation could be a product of intellectual activity of people in all areas of society and is not uncommon that it becomes the subject of a deeper research. The goal of the current research is to present the outcomes of a practical experience to summarize different types of innovation in educational system in Bulgaria and their application in the pedagogical qualification of teachers in all levels of education. The article presents the policy on pedagogical innovation in Bulgaria, presents a classification model for such innovations and the practical experience of implementation in a long-term teacher training. It also presents the inquires on attitudes toward implementation of innovative processes in education conducted among a target group- teachers in different areas of expertise and in different levels of educational system – from kindergarten to 12th grade